Genital Human Papillomavirus Infection in Indian HIV-Seropositive Men Who Have Sex With Men. Issue 2 (March 2017) - Raghavendran, Anantharam; Hernandez, Alexandra L.; Lensing, Shelly; Gnanamony, Manu; Karthik, Rajiv; Sivasubramanian, Murgesan; Kannangai, Rajesh; Abraham, Priya; Mathai, Dilip; Palefsky, Joel M.
Abstract : Background: The incidence of penile cancer in Indian men is high. Little is known about genital human papillomavirus (HPV) infection in Indian HIV-seropositive men who have sex with men (MSM), a population that may be at particularly high risk for genital HPV infection and, potentially, penile cancer. In this study, we assessed the prevalence and risk factors for genital HPV infection in this population. Design and Methods: Three hundred HIV-seropositive MSM were recruited from 2 clinical sites in India. They were tested for genital HPV infection using L1 HPV DNA polymerase chain reaction with probes specific for 29 types and a mixture of 10 additional types. Participants received an interviewer-administered questionnaire that included questions on demographics and behaviors. Results: Human papillomavirus data were available from 299 participants. The prevalence of any HPV type in the penis and scrotum was 55% and 54%, respectively. Human papillomavirus type 35 was the most common oncogenic HPV type followed by HPV-16. In multivariate analysis, being the insertive partner with 100+ male partners increased the odds of any penile HPV infection compared with not being insertive with any partners (odds ratio, 2.5; 95% confidence interval, 1.3–5.1). Circumcision was protective against penile HPV infection (odds ratio, 0.39; 95% confidence interval, 0.19–0.76). Conclusions: The prevalence of penile and scrotal HPV infection was high among Indian HIV-seropositive MSM. The most common oncogenic HPV type in this population, HPV-35, is not included in any currently available HPV vaccines. Insertive anal sex with men and lack of circumcision were the primary risk factors for penile HPV infection in this population. Abstract : A study of penile and scrotal human papillomavirus infection in Indian HIV-seropositive men who have sex with men showed that the prevalence of penile and scrotal human papillomavirus infection was 55% and 54%, respectively.Supplemental digital content is available in the text.